Accounting Information Systems And Human Resources Competence: How To Influence On UMKM Performance In Bandung City - Inta Budi Setya Nusa (Institute of Computer Science (IOCS), 2021)
This study aims to determine how much influence the accounting information system and Human Resource Competence on UMKM performance carried out on UMKM in the city of Bandung. The research method used is descriptive and verification methods with a quantitative approach. The population in this study are the owners and actors of SMEs in the city of Bandung. The sampling technique used is a purposive non-random sampling technique. The method of data analysis in this study uses multiple linear regression analysis which is tested using SPSS 26.0 software for Windows. The results of hypothesis testing in this study indicate that (1) Accounting Information Systems have a positive and significant influence on UMKM Performance (2) and human resource competence has a positive and significant impact on UMKM Performance in Bandung City